Biomphalaria alexandrina as a bioindicator of metal toxicity. (August 2016) - Habib, Mohamed R.; Mohamed, Azza H.; Osman, Gamalat Y.; Mossalem, Hanan S.; Sharaf El-Din, Ahmed T.; Croll, Roger P.
Abstract: Heavy metals are common environmental pollutants to the aquatic ecosystems. Several aquatic species have been used as bioindicators and biomonitoring subjects for heavy metals pollution. In the present study, the effects of cadmium (Cd) and manganese (Mn) on the survival, attachment, locomotion, and feeding behaviours of the gastropod snail Biomphalaria alexandrina were determined. The short-term (96 h) LC50 for Cd and Mn were found to be 0.219 and 154.2 mg/l, respectively. Long-term exposures (16–20 days) to ascending concentrations of Cd (0.01–1 mg/l) and Mn (50–500 mg/l) also caused gradual decreases in the survival rate of B. alexandrina in a dose-dependent manner. Attachment, locomotion and feeding behaviours of snails exposed to lethal and sublethal concentrations of Cd and Mn at acute (96 h) and chronic exposure (24 days) intervals, respectively, were also recorded. Compared to controls, a significant decrease ( p ≤ 0.05) was recorded in the different behaviours of exposed snails. These changes in behaviour would potentially impact the snail's ability to survive in the wild. Although Cd caused a more severe decline in snail survivorship than Mn, the behavioural effects of Mn were much more severe than Cd when the metals were roughly matched for lethality. In sum, the present study demonstrates B. alexandrina to be a sensitive bioindicator and model organism to assess heavy metals risk factors for severe toxicity in freshwater ecosystems. Graphical abstract: Highlights: Heavy metals have major impacts on terrestrial and aquatic communities. Biomphalaria, the snail host of Schistosoma mansoni, is proposed as a bioindicator of metal pollution. B. alexandrina is endemic to Egyptian ecosystems and can be used as to monitor water pollution. Attachment, locomotion and feeding behaviours of B. alexandrina are sensitive measures of Cd and Mn exposure. Behaviour is a more sensitive biomarker than survival for environmental toxicity and risk assessment purposes.